PENGARUH EKONOMI DAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PENINGKATAN PERKARA PERCERAIAN - Herawati, Baiq Candra; Setyawan, Ari; Soraya, Siti; Hidjah, Khasnur; Wardhana, Helna (Juremi: Jurnal Riset Ekonomi, 2024)
Divorce is a break in the relationship or marriage bond caused by several factors such as the economy and domestic violence. The author is interested in conducting this research because he wants to know how much the economy and domestic violence affect the increase in divorce cases in Mataram City. This research method uses quantitative methods with data collection techniques, namely secondary data from the Mataram City Statistics Center Agency. Classical assumption tests and hypothesis tests were carried out. The data analysis method was carried out using multiple linear regression statistical tests. Based on the data analysis that has been carried out, it is known that the economy and domestic violence simultaneously and partially do not affect the increase in divorce.